SISTEM INFORMASI PENGARSIPAN PADA KANTOR DITRESKRIMUM SUBDIT III POLDA SUMATERA UTARA BERBASIS WEBSITE - Lidia Marisa Sianturi; Jamaluddin Jamaluddin; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Archives are reviews that have been written, printed and in various forms made by groups/organizations, individuals and institutions or agencies within a company. The archive contains letters, deeds, scripts, books, charters and so on, which can later be used as evidence for actions and decisions. At the office of the general criminal investigation directorate, sub-directorate III of the North Sumatra Regional Police, the archives are still archived in the agenda book or can be called manually archived, especially in the archiving of incoming and outgoing letters. The research objective is to build a website-based mail filing information system using the waterfall method. This study resulted in several menu sections such as adding letters, changing mail data and uploading letters. In testing the system using the black box method and with the desired results. Thus, the results from the data obtained can be applied to the general criminal investigation directorate office, sub-directorate III of the North Sumatra Regional Police.